Amphiphilic peptide-tagged N-cadherin forms radial glial-like fibers that enhance neuronal migration in injured brain and promote sensorimotor recovery. (March 2023) - Ohno, Yuya; Nakajima, Chikako; Ajioka, Itsuki; Muraoka, Takahiro; Yaguchi, Atsuya; Fujioka, Teppei; Akimoto, Saori; Matsuo, Misaki; Lotfy, Ahmed; Nakamura, Sayuri; Herranz-Pérez, Vicente; García-Verdugo, José Manuel; et al.
Abstract: The mammalian brain has very limited ability to regenerate lost neurons and recover function after injury. Promoting the migration of young neurons (neuroblasts) derived from endogenous neural stem cells using biomaterials is a new and promising approach to aid recovery of the brain after injury. However, the delivery of sufficient neuroblasts to distant injured sites is a major challenge because of the limited number of scaffold cells that are available to guide neuroblast migration. To address this issue, we have developed an amphiphilic peptide [(RADA)3 -(RADG)] (mRADA)-tagged N-cadherin extracellular domain (Ncad-mRADA), which can remain in mRADA hydrogels and be injected into deep brain tissue to facilitate neuroblast migration. Migrating neuroblasts directly contacted the fiber-like Ncad-mRADA hydrogel and efficiently migrated toward an injured site in the striatum, a deep brain area. Furthermore, application of Ncad-mRADA to neonatal cortical brain injury efficiently promoted neuronal regeneration and functional recovery. These results demonstrate that self-assembling Ncad-mRADA peptides mimic both the function and structure of endogenous scaffold cells and provide a novel strategy for regenerative therapy. Graphical abstract: Image 1 Highlights: A novel self-assembling Ncad-mRADA peptide forms a supramolecular hydrogel. mRADA hydrogel incorporates the N-cadherin extracellular domain tagged with mRADA. Ncad-mRADA hydrogel provides a scaffold for neuroblast migration in injured brain. Migrating neuroblasts directly interact with radial-glial-like Ncad-mRADA fibers. Ncad-mRADA promotes neuroblast migration and functional recovery after brain injury.